Trityl Cation Catalyzed Intramolecular Carbonyl-Ene Cyclization and [2+2] Cycloaddition - Nomoto, Yuya; Horinouchi, Ryo; Nishiyama, Nobuo; Nakano, Keiji; Ichikawa, Yoshiyasu; Kotsuki, Hiyoshizo (Synlett, 2017)
An unprecedented metal-free catalytic system composed of trityl halides and thioureas has been found to be a convenient source for the generation of trityl cation species, and this cooperative catalytic system was proved to be highly effective for intramolecular carbonyl-ene cyclization and [2+2] cycloadditions.
Keywords: trityl cation catalysis; intramolecular carbonyl-ene; intramolecular [2+2] cycloaddition; thiourea catalyst